Measuring the Root Determinants of Profitability Based on Murabahah Margins and Musyarakah Profit Sharing - Listiana Sri Mulatsih; Hermiyetti Hermiyetti; Jenita Jenita; Ngurah Pandji Mertha Agung Durya; Hartono Hartono (Kontigensi : Jurnal Ilmiah Manajemen, 2023)
The purpose of this research is to analyze and test the factors that can affect Return on Equity atPT. Bukopin Sharia Bank.These factors include murabahah margin and musharakah profit sharing. This research is included in the category of quantitative descriptive research type with numerical model amd the data sourced from financial reports of PT. Bank Syariah Bukopin from the 2016-2023 period. The data were analyzed with IBM SPSS version 22 and analysis was carried out by several tests such as validity test, reliability test, classic assumption test, linear regression analysis and coefficient of determination test. The results of this study indicate that murabahah margin and musharakah profit sharing have a significant effect on ROE at PT. Bukopin Sharia Bank. The high margin and profit sharing provided by PT. Bank Syariah Bukopin can increase ROE and achieve optimal performance. The findings can be a reference in making policies for companies to increase margin and profit sharing so that customer satisfaction increases.